If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -8x = 86 + -22x Solving 12 + -8x = 86 + -22x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '22x' to each side of the equation. 12 + -8x + 22x = 86 + -22x + 22x Combine like terms: -8x + 22x = 14x 12 + 14x = 86 + -22x + 22x Combine like terms: -22x + 22x = 0 12 + 14x = 86 + 0 12 + 14x = 86 Add '-12' to each side of the equation. 12 + -12 + 14x = 86 + -12 Combine like terms: 12 + -12 = 0 0 + 14x = 86 + -12 14x = 86 + -12 Combine like terms: 86 + -12 = 74 14x = 74 Divide each side by '14'. x = 5.285714286 Simplifying x = 5.285714286
| -4x-9y-5=0 | | -6=.5x-3 | | -4x-8y=7 | | 4y-3x=2 | | 5y-3=y/2 | | 813x-5+20=68 | | 3(2x-17+5)=14 | | 0.05+0.07(100-x)=3.2 | | 2x=8-3y | | h+3/8=1/2 | | 3/5(-5/3) | | y=15-2(10-x) | | d=11 | | d=11 | | (45x^3)+(36x^2)-5x-4=0 | | 1/10-1/5=x-9/2 | | 2x=15+11y | | -2x-3y=4 | | -40-(-16)=x/12 | | y=-10+2(x+6) | | Y=-2/3y-5/3 | | .02(3-x)-.04(x+2)=.34 | | (5x-8)/3=4x+2 | | -45/6+51/3 | | (3x-4)-(x-5)= | | 1/2m=0 | | -18+x-7=10-12+5 | | (1/x)+(6/2x) | | 15+3(2x+9)=60 | | 9x-3y=-6 | | 7y+2y-11=-38 | | (-3/8)+(-5/8) |